Primary outcome of babies with hypoxic ischemic encephalopathy - Rawat, Anil Kumar; Shirke, Rupali Praveen; Chandar, Vipan (International Journal of Contemporary Pediatrics, 2016)
Background: Intrapartum fetal hypoxia followed by hypoxic ischemic encephalopathy (HIE) is a common cause of potentially avoidable brain injury in term infants.This study was conducted in a tertiary care centre and included 119 babies of hypoxic ischemic encephalopathy born in hospital as well as referred from neighbouring areas. Methods: Babies with history of intrapartum hypoxia, delayed cry who required resuscitation at birth and in stage II or III of modified sarnat encephalopathy grade (MSEG) and those who had abnormal intrapartum course were included. After performing clinical neurological assessment further data collection included perinatal maternal characteristics- ante partum and intrapartum complications; morbidity pattern in baby including type of resuscitation, onset of seizure, antiepileptic drug, other co morbidity and short term outcome. Results:Out of 119 babies 19% were born low birth and 6% were IUGR. 47% mother were primi gravida whereas 53% were multigravida, 32% pregnancy were unbooked. Ante partum risk factor was found in 3 cases and Intrapartum risk factor was found in 45 (38%) cases. According to MSEG stage II and III babies were enrolled overall 92% babies had seizure and 60% had on day one only. Single antiepileptic drug controlled seizure in 60% of babies who had seizure additional two and more antiepileptic drug were required in fewer no of cases. During stay most common complication was sepsis, observed in 26% cases followed by DIC in 11% cases and AKI in 7% cases. Majority 59% of babies were discharged, mortality was observed in 12.6% cases and 27% left against medical advice. Conclusions:Maternal perinatal risk factors and effective neonatal intervention may improve outcome in babies with hypoxic ischemic encephalopathy.